Virulence gene typing of Methicillin-susceptible Staphylococcus aureus (MSSA)isolates in Universiti Kebangsaan Malaysia Medical Centre (UKMMC) - Hassriana Fazilla Sapri,; Nurul Azirah Mohamad Sani,; Ainihayati Noordin,; Hui-min Neoh,; Salasawati Hussin, (UKM Medical Molecular biology Institute, UMBI, 2011)
We determined the presence of four virulence genes: (cna, seh, PVL, TSST-1) using multiplex PCR in 880 isolates of methicillin-susceptible Staphylococcus aureus (MSSA) collected from the Universiti Kebangsaan Malaysia Medical Centre (UKMMC) in 2009. We found that 51.59% (454/880) of the strains had cna; 21.82% (192/880) possessed seh; 10.23% (90/880) had PVL and 6.82% (60/880) haboured TSST-1. Although methicillin-susceptible, MSSA carries important virulence genes which could affect patient’s clinical course.